Essential oils mix effect on chicks ileal and caecal microbiota modulation: a metagenomics sequencing approach - Girard, Claire; Chabrillat, Thibaut; Kerros, Sylvain; Fravalo, Philippe; Thibodeau, Alexandre (Frontiers in Veterinary Science, 2024)
Introduction Microbiota plays a pivotal role in promoting the health and wellbeing of poultry. Essential oils (EOs) serve as an alternative solution for modulating poultry microbiota. This study aimed to investigate, using amplicon sequencing, the effect of a complex and well-defined combination of EOs feed supplement on both ileal and caecal broiler microbiota, within the context of Salmonella and Campylobacter intestinal colonization. Material and methods For this experiment, 150-day-old Ross chicks were randomly allocated to two groups: T+ (feed supplementation with EO mix 500 g/t) and T– (non-supplemented). At day 7, 30 birds from each group were orally inoculated with 106 CFU/bird of a Salmonella enteritidis and transferred to the second room, forming the following groups: TS+ (30 challenged birds receiving infeed EO mix at 500g/t) and TS– (30 challenged birds receiving a non-supplemented control feed). At day 14, the remaining birds in the first room were orally inoculated with 103 CFU/bird of two strains of Campylobacter jejuni, resulting in the formation of groups T+C+ and T–C+. Birds were sacrificed at day 7, D10, D14, D17, and D21. Ileal and caecal microbiota samples were analyzed using Illumina MiSeq sequencing. At D7 and D14, ileal alpha diversity was higher for treated birds (p <0.05). Results and discussion No significant differences between groups were observed in caecal alpha diversity (p>0.05). The ileal beta diversity exhibited differences between groups at D7 (p < 0.008), D10 (p = 0.029), D14 (p= 0.001) and D17 (p= 0.018), but not at D21 (p = 0.54). For all time points, the analysis indicated that 6 biomarkers were negatively impacted, while 10 biomarkers were positively impacted. Sellimonas and Weissella returned the lowest (negative) and highest (positive) coefficient, respectively. At each time point, treatments influenced caecal microbiota beta diversity (p < 0.001); 31 genera were associated with T+: 10 Ruminoccocaceae genera were alternatively more abundant and less abundant from D7, 7 Lachnospiraceae genera were alternatively more and less abundant from D10, 6 Oscillospiraceae genera were variable depending on the date and 4 Enterobacteriaceae differed from D7. During all the experiment, Campylobacter decreased in treated birds (p < 0.05). This study showed that EO mix modulates ileal and caecal microbiota composition both before and during challenge conditions, increasing alpha diversity, especially in ileum during the early stages of chick life.